A flexible forward simulator for populations subject to selection and demography - Hernandez, Ryan D. (Bioinformatics, 2008)
This article introduces a new forward population genetic simulation program that can efficiently generate samples from populations with complex demographic histories under various models of natural selection. The program (SFS_CODE) is highly flexible, allowing the user to simulate realistic genomic regions with several loci evolving according to a variety of mutation models (from simple to context-dependent), and allows for insertions and deletions. Each locus can be annotated as either coding or non-coding, sex-linked or autosomal, selected or neutral, and have an arbitrary linkage structure (from completely linked to independent). Availability: The source code (written in the C programming language) is available at http://sfscode.sourceforge.net, and a web server (http://cbsuapps.tc.cornell.edu/sfscode.aspx) allows the user to perform simulations using the high-performance computing cluster hosted by the Cornell University Computational Biology Service Unit. Contact: rhernandez@uchicago.edu Supplementary information: An extensive user's manual, perfor-mance statistics, and comparisons of patterns of genetic variation generated by SFS_CODE to theoretical expectations under various non-stationary demographic histories and models of natural selection are available on the project website: http://sfscode.sourceforge.net.